Meningkatkan Kesehatan, Pendidikan dan Ekonomi Dengan Literasi Digital Pada SDGs 2030 - Br Marbun, Ester Sari; Destiani, Teni Saida; Ichsan Fauzi Rachman (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Digital literacy is important for achieving the 2030 Sustainable Development Goals (SDGs) and how to improve health, education and the economy. Digital literacy refers to the ability to use digital technology effectively and efficiently. Digital literacy can help increase access to health, education and economic services as well as increase community participation in decision-making processes in the context of the SDGs. This article shows some of the ways digital literacy can be applied to improve health through increasing access to health information, improve education through the use of digital technology for learning, and improve the economy through digital business development. Overall, this article shows that digital literacy is the key to achieving the 2030 SDGs and improving health, education and the economy in Indonesia.